RETROSPECTIVE ANALYSIS OF TREATMENT EFFICACY IN PATIENTS WITH CHRONIC WOUNDS - Kasrashvili, H.H.; Ksyonz, I.V.; Гюльмамедов, П.Ф.; Andreev, P.O. (World of Medicine and Biology, 2020)
It is estimated that in developed countries from 1 to 2 % of the population will suffer from chronic wounds throughout their life. The study included the retrospective analysis data on the case histories of 75 patients (40 (53 %) women and 35 (47 %) men who were divided into 8 groups depending on the etiological factor. The other determining factor was the use of local negative pressure in their treatment. In all groups active surgical intervention was used, the preparation of the wound for surgical intervention with the help of negative pressure was faster. As a result, the time of the patient’s staying at the in–patient department reduced and the percentage of autotransplants survival increased. Results of the analysis showed that the use of local vacuum therapy caused statistically significant difference in the mean time of treatment between some groups of patients compared to other groups. The number of eliminated chronic wounds is also statistically significant.
Keywords: chronic wounds; retrospective analysis; etiological factor; local negative pressure